2016
DOI: 10.1007/s10482-016-0812-4
|View full text |Cite
|
Sign up to set email alerts
|

Saccharothrix ghardaiensis sp. nov., an actinobacterium isolated from Saharan soil

Abstract: The taxonomic position of a new Saccharothrix strain, designated MB46, isolated from a Saharan soil sample collected in Mzab region (Ghardaïa province, South Algeria) was established following a polyphasic approach. The novel microorganism has morphological and chemical characteristics typical of the members of the genus Saccharothrix and formed a phyletic line at the periphery of the Saccharothrix espanaensis subcluster in the 16S rRNA gene dendrograms. Results of the 16S rRNA gene sequence comparisons reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…One siderophore, one melanin, one lanthipeptide, Table 1. Phenotypic characteristics of strain AN110305 T and related species of the family Pseudonocardiaceae Taxa: 1, strain AN110305 T ; 2, Goodfellowiella [21,22]; 3, Umezawaea [53,54]; 4, Kutzneria [55][56][57][58]; 5, Saccharothrix [59][60][61][62][63][64]. Data were from this study unless indicated.…”
Section: Whole Genome Sequence Analysismentioning
confidence: 99%
“…One siderophore, one melanin, one lanthipeptide, Table 1. Phenotypic characteristics of strain AN110305 T and related species of the family Pseudonocardiaceae Taxa: 1, strain AN110305 T ; 2, Goodfellowiella [21,22]; 3, Umezawaea [53,54]; 4, Kutzneria [55][56][57][58]; 5, Saccharothrix [59][60][61][62][63][64]. Data were from this study unless indicated.…”
Section: Whole Genome Sequence Analysismentioning
confidence: 99%
“…The arid soils of the Algerian Sahara have been shown to be rich in members of the Saccharothrix genus (Sabaou et al, 1998, Zitouni et al, 2005) including new species, such as Saccharothrix algeriensis NRRL B-24137 T (Zitouni et al, 2004a), Saccharothrix hoggarensis DSM 45457 T , Saccharothrix saharensis DSM 45456 T , Saccharothrix tamanrassetensis DSM 45947 T (Boubetra et al, 2013a, Boubetra et al, 2013b, Boubetra et al, 2015), Saccharothrix isguenensis DSM 46885 T and Saccharotrix ghardaiensis DSM 46886 T (Bouznada et al, 2016, Bouznada et al, 2017). In addition, many studies have shown the ability of Saccharothrix strains isolated from these soils to produce new or known antibiotics, such as dithiolopyrrolones (Lamari et al, 2002, Bouras et al, 2008, Merrouche et al, 2011), anthracyclines (Zitouni et al, 2004b) and chloramphenicol (Aouiche at al., 2012).…”
Section: Introductionmentioning
confidence: 99%